Exploring parental understanding of gender diversity in high schools – literature-based study. - John Chaka (International Journal of Studies in Psychology)
For a long time now, high school trans learners have been subject to discrimination because their gender identity does not align with the gender assigned to them at birth. This study explored how parents' understanding of gender can promote gender diversity in high schools. Parents' reactions to their children ‘coming out’ as transgender were used as a proxy to determine what parents' understanding of gender is and whether they can promote gender diversity in high schools. This literature-based study draws from the literature review chapter of a doctoral thesis. The literature search for this study was carried out using various databases, such as EBSCOhost, ScienceDirect, and SABINET. Additional literature searches were completed using the University of the Free State’s online and physical libraries. The findings of this study show a trend of parents taking an affirming stance towards transgenderism and inclining to challenge the established binary systems of gender. However, more studies are needed in the South African school context to explore parents' understanding of gender more deeply.